Aspek Hukum Pengoperasian Pesawat Udara Tanpa Awak Menurut Hukum Positif di Indonesia - Rahman Amin; Muhammad Fikri Al Aziz; Iren Manalu; Ishanti Nurjanah Rahayu R (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Nowadays, unmanned aircraft are widely used in various activities of human life, not only for military purposes, but also for civilian purposes. In addition to providing benefits, the use of unmanned aircraft can create security and safety vulnerabilities for manned aircraft flights and cause other problems. Therefore, it is urgent to study the legal provisions of unmanned aircraft and the problems that can arise in their operation. This research is normative juridical, with a statutory approach. Techniques for collecting legal materials through literature study. The results of the study indicate that the operation of unmanned aircraft is required to comply with the provisions on air space in Indonesia, pass operator or remote pilot certification, register the unmanned aircraft used, as well as other technical matters before and during its operation.Problems that can be caused in the operation of unmanned aircraft, namely problems while in the air, namely collisions with manned aircraft and violations of air space provisions, problems on the ground, namely the fall of an unmanned aircraft on people or objects below it, and other problems related to rights. privacy, copyright, use of r